An evaluation of the effectiveness of psychological therapy in reducing general psychological distress for adults with autism spectrum conditions and comorbid mental health problems. (26th July 2017) - Blainey, Sarah H.; Rumball, Freya; Mercer, Louise; Evans, Lauren Jayne; Beck, Alison
Abstract : Objective: To investigate the effectiveness of psychological therapy in reducing psychological distress for adults with autism spectrum conditions (ASC) and co‐morbid mental health conditions in routine clinical practice. To explore the effect of individual characteristics and service factors on change in general distress. Method: In a specialist psychological therapies service for adults with ASC, the Clinical Outcomes in Routine Evaluation‐Outcome Measure (CORE‐OM) self‐report questionnaire of psychological distress is completed by clients at start and end of therapy. Change over time and reliable and clinical change was assessed for 81 of a total of 122 clients (66.4%). Factors which may influence change over time were explored using available clinical information. Results: Overall, there was a significant reduction in CORE‐OM score during therapy with a small effect size. Most clients showed an improvement in psychological distress over therapy (75.4% improved, with 36.9% of these showing reliable changes). Significant and comparable reductions from pre‐therapy to post‐therapy were seen across the sample, showing that individual differences did not mediate therapy effectiveness. CORE‐OM scores mediate the association between age of ASD diagnosis and hours of therapeutic input required, with greater age at diagnosis and higher distress associated with longer therapy duration. Conclusions: Our preliminary findings suggest that psychological therapy may be effective in reducing general distress for clients with ASC and co‐morbid mental health conditions and should be routinely offered. Individuals who are diagnosed with ASD in adulthood are likely to require a longer course of therapy when their general distress scores are high.